Molecular nano-I-beam class of materials: options based on configuration, first principles-based optimization and properties - Salah A. M. Elmoselhy (Scientific Reports)
Abstract Nanotubes showed merits including high structural strength-to-weight ratio. However, tubes are less favored regarding stiffness and strength. Nano-I-beams are proposed for improved nano-mechanics. Computationally, the study proposes novel molecular designs of I-beam-like shaped structures. A conformation analysis, molecular dynamics and first principles-based optimization are presented. The study proposes options based on the configuration of the molecular nano-I-beam structure providing less number of planes of symmetry and hence more stability than nanotube-like structures. These designs feature a unique geometrical differentiator of having the walls of the out-of-plane hexagonal motif-based molecular nano-I-beam (C60H46) inclined with different inclination angles enabling promising properties. The stability of the proposed nano-I-beam is proved on par with the corresponding nanotube-like structure. First principles-based evidence is provided on the comparable polarizability and the comparable ability to store energy of the supercell of the crystalline slab nano-I-beam in comparison with the corresponding nanotube. A proposed hybrid octa-hexagonal-cubic molecular nano-I-beam (C24H12) remedies the nano-buckling observed in the alike square-octagonal nanostructure. The molecular nano-I-beam exhibits intrinsic switchability that enables the nano-I-beam to be a topological semiconductor/insulator. The results show promising electronic and elastic properties of the proposed nano-I-beams that suit several applications such as their use in capacitors, transistors, insulators, batteries, quantization-based nano-devices, solid lubricant additive to grease, toughening fibers of nanocomposites, hydrophobic films, emissions adsorbents, catalytic sensors, PAH materials for space, and sustainable energy. The molecular nano-I-beam provides the base of the corresponding 2-D crystalline slab nano-I-beams.